Production method of conductive fiber
By using the solvent-free method of surfactant-free on synthetic fibers, the problem of insufficient adhesion of single-wall carbon nanotube conductive film is solved by using the high polarity and high permeability of aprotic solvents, and the improvement of conductive properties and interface bonding strength is achieved.
Patent Information
- Application Number
- JP2023120624
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, the adhesion of the single-wall carbon nanotube conductive film on the synthetic fibers is insufficient, resulting in a decrease in conductivity, and the interface bonding strength between the polyester fiber and the carbon nanotube is weak, making peeling prone.
Using a solvent-free method without surfactant, single-walled carbon nanotubes are dispersed in an aprotic solvent to make conductive ink. Through impregnation and vacuum drying processes, the conductive film is firmly adhered to the surface of the synthetic fibers, and the high polarity and high permeability of the aprotic solvent are used to improve interface bonding.
The firm adhesion of the single-wall carbon nanotube conductive film on the synthetic fiber is achieved, the conductive properties and interface bonding strength are improved, and the conductive properties are avoided.
Smart Images

Figure 2025017534000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing conductive fibers. [Background technology]
[0002] Single-walled carbon nanotubes (SWCNTs) have excellent mechanical, electrical and thermal properties, and are also highly flexible. For this reason, SWCNT films containing SWCNTs are expected to be used as next-generation flexible conductive materials.
[0003] Many studies have been conducted on the lamination of SWCNT conductive films on the surface of synthetic fibers to provide them with conductive fabric functionality. Patent Document 1 discloses a technique for forming SWCNT conductive films on synthetic fibers using a dispersion liquid containing SWCNTs, a binder, and a surfactant as a dispersant for SWCNTs. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-059561 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in Patent Document 1, the binder component and the surfactant component added as a dispersant remain in the formed SWCNT conductive film. Since these components are non-conductive, it is thought that the electrical properties such as the electrical conductivity of the SWCNT conductive film will decrease. In addition, there is an issue that the adhesive strength at the interface is weak and peeling occurs when it comes to polyester fibers (PET fibers), which have high crystallinity and stable surface properties, and the properties of SWCNT are not fully utilized.
[0006] The present invention has been made in consideration of the problems inherent in the conventional techniques, and an object of the present invention is to provide a method for producing conductive fibers in which a carbon nanotube conductive film is firmly attached to synthetic fibers. [Means for solving the problem]
[0007] The method for producing conductive fibers according to this embodiment is a method for producing conductive fibers comprising synthetic fibers and a conductive film containing single-walled carbon nanotubes formed on the surface of the synthetic fibers, and includes a conductive ink immersion process in which the synthetic fibers are immersed in a conductive ink in which single-walled carbon nanotubes are dispersed in an aprotic solvent to adhere to the synthetic fibers, and a solvent removal process in which, after the conductive ink immersion process, the synthetic fibers to which the conductive ink has been adhered are dried and the aprotic solvent is removed. Effect of the Invention
[0008] According to the present invention, it is possible to provide a method for producing conductive fibers in which a carbon nanotube conductive film is firmly attached to synthetic fibers. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a conductive fiber according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged view showing a schematic diagram of a synthetic fiber according to the present embodiment in which an aprotic solvent has been permeated. [Diagram 3] 1 is a schematic diagram showing a method for producing a conductive fiber according to an embodiment of the present invention. [Figure 4A] This is an enlarged SEM photograph of the surface condition of synthetic fiber (PET fiber). [Figure 4B] FIG. 4B is an enlarged SEM photograph of the surface state of the conductive fiber made from the synthetic fiber in FIG. 4A. [Figure 5A] This is an enlarged SEM photograph of the surface condition of synthetic fiber (PET fiber). [Figure 5B] 5B is an SEM photograph showing an enlarged view of the surface state of the conductive fiber made from the synthetic fiber in FIG. 5A. [Figure 6A]1 is an optical image showing a conductive fiber according to an embodiment of the present invention. [Figure 6B] 1 is an optical image showing a conductive fiber having a conductive film on the surface of a round cross-section fiber. [Figure 7] FIG. 1 is a schematic diagram of an experiment for measuring sheet resistance. [Figure 8] FIG. 1 is a schematic diagram of an experiment for measuring electromagnetic wave shielding properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The method for producing a conductive fiber according to the present embodiment will be described in detail below with reference to the drawings. Note that the dimensional ratios in the drawings are exaggerated for the sake of convenience and may differ from the actual ratios.
[0011] [Conductive fiber] 1 comprises synthetic fiber 10 and a conductive film 20 containing single-walled carbon nanotubes (hereinafter, SWCNTs) 25 formed on the surface of synthetic fiber 10. Conductive ink 24, in which SWCNTs 25 are dispersed in aprotic solvent 23, is immersed in and adhered to synthetic fiber 10, resulting in conductive fiber 1 in which conductive film 20 is firmly adhered to synthetic fiber 10.
[0012] (Synthetic Fibers) The synthetic fiber 10 is not particularly limited, but is preferably at least one selected from the group consisting of polyester fibers, polyamide (nylon) fibers, polyolefin fibers, acrylic fibers, polyurethane fibers, and cellulose fibers. Among these, polyethylene terephthalate fibers (hereinafter, PET fibers), which are a type of polyester fiber, are easily permeated with conductive ink 24 in which SWCNTs 25 are dispersed in an aprotic solvent 23, and conductive film 20 is easily attached. For this reason, polyester fibers are more preferable as the synthetic fiber 10, and PET fibers are even more preferable. The structure of PET fibers is shown in Chemical Formula 1.
[0013] [ka]
[0014] (Conductive film) The conductive film 20 contains SWCNTs. The SWCNTs 25 contained in the conductive film 20 have a median diameter of, for example, 0.5 nm to 5 nm, and from the viewpoint of electrical conductivity, preferably 1 nm to 3 nm. The SWCNTs 25 contained in the conductive film 20 have a length of, for example, 1 μm to several tens of μm. The conductive film 20 has a thickness of, for example, 50 nm to 500 nm, and from the viewpoint of adhesion at the interface with the synthetic fiber 10, preferably 100 nm to 200 nm.
[0015] A conductive ink 24 having SWCNTs 25 dispersed in an aprotic solvent 23 is immersed in and adhered to a synthetic fiber 10, and then the synthetic fiber 10 is dried to remove the aprotic solvent 23, thereby firmly adhering a conductive film 20 containing SWCNTs to the surface of the synthetic fiber 10.
[0016] The conductive fiber 1 is manufactured by the conductive fiber manufacturing method described below.
[0017] [Method of manufacturing conductive fibers] The method for producing conductive fibers is a method for producing conductive fiber 1 having synthetic fiber 10 and conductive film 20 containing SWCNTs 25 formed on the surface of synthetic fiber 10. The method for producing conductive fiber 1 includes a conductive ink immersion step and a solvent removal step.
[0018] (Conductive ink dipping process) The conductive ink dipping step is a step of dipping synthetic fibers 10 in conductive ink 24, in which SWCNTs 25 are dispersed in an aprotic solvent 23, to adhere the synthetic fibers 10 to the conductive ink 24, as shown in FIG.
[0019] An aprotic solvent 23 is used as a dispersion solvent for the conductive ink 24. The aprotic solvent 23 is preferably at least one selected from the group consisting of DMF (N,N-dimethylformamide), DMSO (dimethylsulfoxide), DMA (N-methylacetamide), and acetonitrile. Both the aprotic solvent 23 and the SWCNTs 25 have high polarity, and the SWCNTs 25 are uniformly dispersed in the aprotic solvent 23 even without the addition of a dispersant such as a surfactant, resulting in a good conductive ink containing only the SWCNTs 25. When the synthetic fibers 10 are PET fibers, DMF is more preferable from the viewpoint of easy penetration into the interior of the PET fibers.
[0020] DMF is an amide formed by condensation of formic acid and dimethylamine. Amide bonds are relatively stable bonds and do not easily react with nucleophiles or electrophiles, so it is used as an organic solvent. It is highly polar because it has a carbonyl group, and is therefore called an aprotic polar solvent. On the other hand, SWCNT25 is highly polar and has high stereoregularity, and exhibits the property of easily attracting and agglomerating molecules. DMF molecules contain amide bonds, and since amide bonds and carbon are easily adsorbed, a conductive ink24 in which SWCNT25 are uniformly dispersed in the DMF solvent can be obtained without the addition of a dispersant such as a surfactant.
[0021] The solubility parameter (SP value) of DMF is 12.0, which is close to the solubility parameter of PET fiber, 10.7. Therefore, DMF easily penetrates into the amorphous part inside crystalline polymers with stable surfaces such as PET fiber, causing swelling and softening of the PET fiber surface, and the PET fiber surface is modified. This change in the surface state of the PET fiber caused by DMF has a significant effect on the adhesion at the interface.
[0022] The SP value is an index that represents the strength of the intermolecular forces (cohesive energy density) of a substance, and is expressed as 1 cm 3 It is expressed as the square root of the heat of vaporization required for a liquid to evaporate. Substances with similar SP values (σ) tend to mix easily and have a high solubility. SP value ((cal / cm 3 ) 1 / 2) can be calculated from the following formula (1). SP = ((ΔH-RT) / V) 1 / 2 =(d / M (CE)) 1 / 2 (1)
[0023] In the above formula (1), the latent heat of vaporization of the compound is ΔH (cal / mol), the gas constant is R (cal / mol), the absolute temperature is T (K), and the molar volume is V (cm 3 / mol), density d(g / cm 3 ), gram molecular weight (g / mol), and cohesive energy CE (cal / mol).
[0024] As shown in Figure 2, synthetic fiber 10 (PET fiber) has a microphase separation structure with crystalline portion 11 and amorphous portion 12. When aprotic solvent 23 (DMF) acts on this, DMF penetrates into amorphous portion 12 of PET fiber, causing softening and swelling. This action causes molecular movement to become more active as the temperature increases, and penetrates deeper into the fiber. Since the glass transition temperature of PET fiber is 70°C, when the temperature is 70°C or higher, the molecular movement of crystalline portion 11 also becomes active, and DMF penetrates into crystalline portion 11, causing the crystal structure to collapse, and the dispersion of crystal grains becomes unstable during recrystallization, which may cause a decrease in physical properties. Therefore, the action of DMF needs to be performed at a temperature of 70°C or lower in order to maintain the physical properties of PET fiber.
[0025] In addition, the interface between the PET fiber and the SWCNTs becomes entangled at the surface layer due to the softening and swelling of the PET fiber. When the DMF is removed, the PET fiber returns to its original state, improving the adhesive strength of the interface and forming a strong conductive film made of SWCNTs alone.
[0026] As described above, the conductive ink 24 does not require a dispersant and may not contain a surfactant. If the surfactant component added as a dispersant remains in the conductive film as in the conventional method, the surfactant component is non-conductive, and this may reduce the electrical properties, such as the electrical conductivity, of the conductive film. Therefore, by not including a surfactant in the conductive ink 24, a conductive fiber 1 having higher electrical properties than conventional methods can be produced.
[0027] The method for preparing the conductive ink 24 in which the SWCNTs 25 are dispersed in the aprotic solvent 23 is not particularly limited. In order to improve the dispersibility of the SWCNTs 25 in the aprotic solvent 23, the SWCNTs 25 can be pulverized using a pulverizer such as a ball mill, a rotor speed mill, a cutting mill, a homogenizer, a vibration mill, or an attritor, and dispersed in the aprotic solvent 23. Both the aprotic solvent 23 and the SWCNTs 25 have high polarity, and the SWCNTs 25 can be uniformly dispersed in the aprotic solvent 23 without the addition of a dispersant such as a surfactant. In the aprotic solvent 23, the wettability of the SWCNTs 25 is improved, and the SWCNTs 25 can be finely disintegrated.
[0028] The method for immersing and attaching the conductive ink 24 to the synthetic fibers 10 is not particularly limited, and a general impregnation treatment method such as a treatment method involving applying micro-vibrations can be used. However, applying micro-vibrations increases the temperature of the conductive ink 24, making it easier for the aprotic solvent 23 to penetrate into the synthetic fibers 10 and increasing its attack on the synthetic fibers 10, which is thought to cause dissolution of the synthetic fibers 10, changes in the crystal structure, and deterioration of the physical properties.
[0029] Therefore, as a method for immersing the conductive ink 24 in the synthetic fibers 10 and attaching it thereto, it is preferable to use a ball mill 50 as shown in FIG. 3. In order to form a uniform conductive film 20 on the synthetic fibers 10 while maintaining the dispersibility of the SWCNTs 25 in the aprotic solvent 23, the synthetic fibers 10 and the conductive ink 24 are put into the ball mill 50, and the conductive ink 24 is dispersed on the synthetic fibers 10 while stirring. A certain amount of balls 51, which are a dispersion medium, are put into the cylindrical container of the ball mill 50. Then, when the ball mill 50 is rotated around the horizontal axis, the balls 51 are lifted to a certain height along the inner wall as the cylindrical container rotates, and circulate in a certain direction within the cylindrical container by sliding and rolling down the inner wall. A uniform conductive film 20 can be formed on the synthetic fibers 10 during the circulation of the balls 51. The method using such a ball mill 50 causes almost no temperature rise, prevents the aprotic solvent 23 from penetrating into the interior of the synthetic fibers 10, and enables the conductive film 20 to be laminated on the synthetic fibers 10 while suppressing deterioration of the physical properties of the synthetic fibers 10.
[0030] The concentration of SWCNTs 25 in the conductive ink 24 is preferably 0.01 to 0.5 mass%, more preferably 0.05 to 0.2 mass%, and even more preferably 0.08 to 0.12 mass%, based on 100 mass% of the conductive ink 24. When the concentration of SWCNTs 25 is within the above range, a uniform conductive film 20 is easily formed.
[0031] Before the conductive ink dipping process, a pretreatment process may be performed in which the synthetic fibers are dipped in polydopamine (PDA). PDA mimics a protein called the byssus of the mussel (a type of bivalve), and is a catechol-based polymer that has catechol groups, amino groups, and benzene rings and bonds to various materials. It can change the surface properties of hydrophilic cotton fibers and hydrophobic PET fibers, improving adhesion to conductive films containing SWCNTs. PDA is a polymer formed by the self-polymerization of dopamine as it oxidizes under alkaline conditions in an oxygen atmosphere. The dopamine shown on the left side of chemical formula 3 becomes the PDA shown on the right side via an intermediate.
[0032] By carrying out a pretreatment step of immersion in PDA, it is possible to modify the surface of the fiber to be hydrophilic or hydrophobic through interactions with the dopamine derivative (hydrogen bonds, π-π interactions, etc.). In particular, it is preferable to carry out a pretreatment step of immersion in PDA for cotton fiber, which is a type of cellulose fiber with hydroxyl groups as shown in Chemical Formula 2, since it has high water absorption. Pretreatment with PDA allows the hydroxyl groups of the cotton fiber to hydrogen bond with each other, modifying the surface to be hydrophobic, and improving adhesion to hydrophobic SWCNTs.
[0033] [ka]
[0034] [ka]
[0035] When a pretreatment process is performed in which the PET fibers are immersed in PDA, the PET fibers have some water absorption, which causes π-π interactions between the PET fibers and the benzene rings present in the dopamine, improving the hydrophobicity and improving the adhesion at the interface.
[0036] (Solvent removal process) The solvent removal step is a step in which, after the conductive ink immersion step, the synthetic fibers 10 with the conductive ink 24 attached thereto are dried and the aprotic solvent 23 is removed. As described above, when the temperature of the synthetic fibers 10 exceeds the glass transition temperature, the movement of molecules in the crystalline portion becomes active, the solvent penetrates into the crystals, the crystal structure collapses, and when the synthetic fibers 10 are recrystallized, the dispersion of the crystal grains becomes unstable, which may cause a decrease in physical properties. For this reason, the temperature in the solvent removal step is preferably equal to or lower than the glass transition temperature of the synthetic fibers 10.
[0037] From the viewpoint of the adhesion of the conductive film 20 to the synthetic fiber 10, it is preferable to use a vacuum drying method for the solvent removal process. For example, when DMF is used as the aprotic solvent 23 and PET fiber is used as the synthetic fiber 10, the boiling point of DMF is 153°C, so a drying condition of 150°C or higher is required to remove DMF from the PET fiber. However, if the temperature is raised to the glass transition temperature of 70°C or higher of the PET fiber, DMF will penetrate into the crystalline structure of the PET fiber, and the physical properties of the PET fiber will deteriorate. Therefore, it is preferable to adopt vacuum drying and remove the solvent at a temperature of 70°C or lower. During drying, the PET fiber swollen by DMF shrinks to its original state, and the adhesion of the interface can be strengthened during this process.
[0038] As described above, the method for producing the conductive fiber 1 according to this embodiment is a method for producing the conductive fiber 1 including the synthetic fiber 10 and the conductive film 20 containing SWCNTs 25 formed on the surface of the synthetic fiber 10. The method for producing the conductive fiber 1 includes a conductive ink immersion step of immersing the synthetic fiber 10 in a conductive ink 24 in which SWCNTs 25 are dispersed in an aprotic solvent 23 to adhere to the synthetic fiber 10, and a solvent removal step of drying the synthetic fiber 10 to which the conductive ink 24 has been adhered and removing the aprotic solvent 23 after the conductive ink immersion step. According to the method for producing the conductive fiber 1 according to this embodiment, it is possible to provide a method for producing the conductive fiber 1 in which a carbon nanotube conductive film is firmly adhered to the synthetic fiber 10.
[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0040] [Example] (Conductive ink dipping process) The synthetic fibers used were four types of PET fibers manufactured by Teijin Frontier Co., Ltd.: Calcuro (registered trademark), Nanofront (registered trademark), Octa (registered trademark), and Wavelon (registered trademark). All of the PET fibers have the following characteristics in their cross-sectional shape and fiber diameter, unlike conventional PET fibers with a round cross-section, in order to impart sweat absorption and quick drying properties. Calcuro has an irregular cross-sectional shape with deep grooves. Nanofront is an ultra-fine fiber with a diameter of 700 nm, and has a surface area several ten times that of normal fibers. Octa has an octopus-shaped cross-section with eight protrusions arranged radially on a hollow fiber with holes. Wavelon has a flat cross-section with four peaks.
[0041] As raw materials for the conductive ink, we prepared SWCNTs (eDIPS EC1.5, manufactured by Meijo Nano Carbon Co., Ltd., with a central diameter of 1 to 3 nm) and DMF, an aprotic solvent, without the addition of a dispersant. Using an ultrasonic homogenizer, SWCNTs were dispersed in DMF so that the SWCNT content was 0.1% by mass, to prepare the conductive ink. The ultrasonic homogenizer conditions were a pulse cycle of 5 seconds, amplitude control of 200 W, and processing for 1 hour.
[0042] The conductive ink was applied to the PET fibers by immersion using a ball mill at a speed of 350 rpm for 30 minutes.
[0043] (Solvent removal process) The PET fibers with the conductive ink applied were dried at about 26°C for about 6 hours using a vacuum drying method to remove the DMF, resulting in conductive fibers with a conductive film containing SWCNTs formed on the surface of the PET fibers.
[0044] Figure 4A shows SEM images of the PET fiber before and after the conductive film was formed when Calcuro was used, and Figure 4B shows SEM images of the PET fiber after the conductive film was formed. Figure 5A shows SEM images of the PET fiber before and after the conductive film was formed when Nanofront was used, and Figure 5B shows SEM images of the PET fiber before and after the conductive film was formed.
[0045] As shown in Figure 4B, it was confirmed that SWCNTs were entangled and attached to each individual PET fiber. Because the SWCNTs were directly entangled with the PET fibers, the adhesion at the interface was stronger. This is believed to be because the PET fibers used had an irregular cross-sectional shape with deep grooves on the surface and a random single-filament cross-sectional shape in the axial direction, resulting in large interfiber voids that made it easier for the SWCNTs to entangle. In addition, the presence of voids between the PET fibers allowed DMF to easily penetrate deep into the PET fibers, enabling the conductive film to cover the entire PET fiber, resulting in good adhesion.
[0046] On the other hand, in Figure 5B, it was confirmed that the conductive film was densely layered, covering the aggregated PET fibers. This is presumably because the PET fibers used were ultrafine fibers with a diameter of 700 nm, which gave the fibers a large surface area and surface characteristics with high adsorption and gripping properties (high friction), and the fine irregularities on the fiber surface had an anchoring effect, improving the adhesion at the interface.
[0047] In this way, by taking advantage of the characteristic cross-sectional shape of the PET fiber, the adhesion at the interface was improved through the anchor effect and the expanded contact area effect, making it easier for the PET fiber and SWCNTs to become entangled, and enabling the conductive film to be firmly attached to the PET fiber.
[0048] Figure 6A is an optical image showing a conductive fiber made using PET fibers (Wavelon, Octa, Calcuro, Nanofront). Meanwhile, Figure 6B is an optical image showing a conductive fiber made in the same manner as above using PET fibers (fiber diameter 50 μm) with a round cross section that are commonly used as automobile airbag deployment covers. The conductive fiber shown in Figure 6A has a smaller fiber diameter and a larger surface area than the conductive fiber shown in Figure 6B, so it was found that the conductive film was uniformly laminated over the entire surface of the PET fiber.
[0049] (evaluation) The obtained test samples of conductive fibers were evaluated by the methods described below.
[0050] <Sheet resistance measurement> The sheet resistance of the conductive film of the conductive fiber was measured by the Van der Pauw method. As shown in Figure 7, the magnitude of the current when a current source is connected between two terminals and the resistance R1 and R2 due to the potential difference between the other two terminals are calculated, and the correction coefficient f, which is determined by the ratio of the resistances R1 and R2 (R1>R2), is obtained from a mathematical table. The sheet resistance Rs (Ω) was then calculated by solving the following formula (2). Rs=(π / ln2)·(R1+R2) / 2·f(R1 / R2) (2)
[0051] [Table 1]
[0052] The results of measuring the sheet resistance (average of n=5) for conductive fibers made using PET fibers (Calcuro, Nanofront, Octa, Wavelon) by immersing the conductive ink once using a ball mill are shown in Table 1. When Calcuro was used for the PET fibers, the lowest value of 10.8Ω / sq. was obtained, indicating that the fibers have good conductivity. When Calcuro was used for the PET fibers, the sheet resistance was stable with small variations between samples, being 10.8Ω / sq. for the first run, 11.8Ω / sq. for the second run, 8.4Ω / sq. for the third run, 11.7Ω / sq. for the fourth run, and 5.2Ω / sq. for the fifth run. This is thought to be because, as shown in Figure 4B, SWCNTs are entangled and attached to each PET fiber, resulting in good electrical conductivity on the surface and stable properties.
[0053] <Electromagnetic wave shielding> The electromagnetic shielding properties of the conductive fiber were evaluated. Specifically, as shown in Fig. 8, a vector network analyzer (VNA) 60 and a waveguide 63 were connected with a coaxial cable 61, and the conductive fiber was sandwiched between the waveguide 63 as a shielding material 62 to measure the shielding effectiveness (SE). The shielding effectiveness SE (dB) can be calculated from the following formula (3), and was obtained from the intensity ratio of the input wave E1 from port 1 and the output wave E4 from port 2. SE=20 log10 (E4 / E1) (3)
[0054] The sheet resistance and shielding effectiveness SE of conductive fibers (hereinafter, "four-time immersion product") made by repeatedly immersing PET fibers (Calcuro) in conductive ink using a ball mill four times were measured.
[0055] The sheet resistance of the sample dipped four times was 2.6 Ω / sq. As shown in Table 1, the sheet resistance of the conductive fiber (Calcuro) produced by dipping once in conductive ink was 10.8 Ω / sq., whereas the sheet resistance of the sample dipped four times was further reduced.
[0056] Meanwhile, when the electromagnetic shielding properties of the sample immersed four times were measured, the shielding effect SE was -33 dB. Since a shielding effect SE of -20 dB or less is generally recommended, the sample immersed four times achieved a good shielding effect. As shown in Figure 4B, the conductive fiber has SWCNTs entangled and attached to each individual PET fiber. It is believed that by immersing the PET fiber in the conductive ink four times, the amount of SWCNTs attached to the PET fiber further increased, further improving the electrical conductivity of the surface, resulting in a conductive fiber with a stable electromagnetic shielding effect.
[0057] Although the present embodiment has been described above, the present embodiment is not limited to this, and various modifications are possible within the scope of the gist of the present embodiment. [Explanation of symbols]
[0058] 1. Conductive fiber 10 Synthetic Fibers 11 Crystal part 12 Amorphous part 20 Conductive Film 23 Aprotic Solvents 24 Conductive ink 25 Single-walled carbon nanotubes (SWCNTs) 50 Ball Mill
Claims
1. Synthetic fibers and A method for producing a conductive fiber comprising: a conductive film including single-walled carbon nanotubes formed on a surface of the synthetic fiber, the method comprising: a conductive ink immersion step of immersing the synthetic fibers in a conductive ink in which the single-walled carbon nanotubes are dispersed in an aprotic solvent, thereby allowing the synthetic fibers to adhere to the conductive ink; a solvent removal step of drying the synthetic fibers to which the conductive ink has been applied and removing the aprotic solvent after the conductive ink immersion step; The method for producing a conductive fiber comprising the steps of:
2. The method for producing a conductive fiber according to claim 1 , wherein the synthetic fiber is a polyester fiber.
3. The method for producing conductive fibers according to claim 1 or 2, wherein the aprotic solvent is N,N-dimethylformamide.
4. The method for producing conductive fibers according to claim 1 or 2, further comprising a pretreatment step of immersing the synthetic fibers in polydopamine prior to the conductive ink immersion step.
5. The method for producing conductive fibers according to claim 1 or 2, wherein the temperature in the solvent removal step is equal to or lower than the glass transition temperature of the synthetic fibers.
6. The method for producing conductive fibers according to claim 5 , wherein the solvent removal step uses a vacuum drying method.
7. The method for producing conductive fibers according to claim 1 or 2, wherein a ball mill is used in the conductive ink immersion step.
8. The method for producing conductive fibers according to claim 1 or 2, wherein the conductive ink does not contain a surfactant.
Citation Information
Patent Citations
Electroconductive fibers with carbon nanotubes deposited thereon, electroconductive threads, fiber structure, and process for producing same
JP2010059561A